To simplify the expression, we can divide the numerator and denominator separately.
Let's divide the numerator first: 7x^4y^2z / x^2yz.
Dividing x^4 by x^2, we subtract the exponents: x^4 ÷ x^2 = x^(4-2) = x^2.
Dividing y^2 by y, we subtract the exponents: y^2 ÷ y = y^(2-1) = y^1 = y.
Combining the results, we have 7x^2yz in the numerator.
Now let's divide the denominator: x^2yz.
Dividing x^2 by x^2, we subtract the exponents: x^2 ÷ x^2 = x^(2-2) = x^0 = 1.
Dividing y by y, we subtract the exponents: y ÷ y = y^(1-1) = y^0 = 1.
Combining the results, we have 1xyz in the denominator.
Therefore, the simplified expression is: 7x^2yz / xyz.
The xyz in the numerator and denominator cancel each other out: xyz / xyz = 1.
Thus, the final simplified expression is: 7x^2 / 1.
Therefore, the simplified expression is 7x^2.
7x^4y^2z/x^2yz
1 answer